Clinical features and outcomes of hepatocellular carcinoma in Caucasian cirrhotic patients on long‐term analogue therapy for hepatitis B. Issue 4 (19th June 2018) - Loglio, A.; Iavarone, M.; Grossi, G.; Viganò, M.; Rumi, MG.; Facchetti, F.; Lunghi, G.; Sangiovanni, A.; Colombo, M.; Lampertico, P.
Summary: Background: Long‐term oral nucleos(t)ide analogue (NUC) therapy in hepatitis B virus (HBV)‐related compensated cirrhotics prevents clinical decompensation but not hepatocellular carcinoma (HCC) development. Aims: To define the clinical features and outcomes of HCC in long‐term NUC‐treated HBV patients. Methods: All HCCs developing between 2005 and 2016 in NUC‐treated HBV patients under surveillance were studied, excluding those that occurred within the first 6 months of therapy. Clinical features of HCC, alpha faetoprotein (AFP) patterns and patients' outcome were studied. Results: Seventy‐six HCC patients were included. Median age was 67 (40‐83) years, 84% males, 96% Caucasian, 95% HBeAg‐negative, 96% with undetectable HBV DNA, 83% with normal ALT levels, and 92% with compensated cirrhosis. Median serum AFP levels were 4 (1‐3615) ng/mL (>7 ng/mL in 36%). HCC was monofocal in 78%, had a median diameter of 20 (6‐57) mm and was in its early stage in 92% which allowed potentially curative treatments in 78% (39% ablation, 28% surgical resection, 11% liver transplantation). Overall, a complete response was obtained in 61 (80%) patients: in 40 after a first‐line treatment, in 3 after the second–line treatment, in 2 after the third‐line treatment, while 16 underwent liver transplantation (8 as second line). During 45 (7‐144) months after HCC diagnosis, 19 patients died, 84% from HCC progression. The median time to recurrence was 20.2 (3‐53) months, and the cumulative 5‐year liver‐related survival was 74%. Conclusions: HCCs developing in patients under long‐term NUC treatment were single, small tumours, amenable to curative therapies able to confer excellent 5‐year survival rates.